Reliability of functional knee tests in normal athletes - Risberg, M. A.; Holm, I.; Ekeland, A. (Scandinavian Journal of Medicine & Science in Sports, 1995)
Functional tests are used to determine functional limitations in patients with anterior cruciate ligament injuries. The reproducibility of 4 such functional tests was determined in 21 normal athletes. The athletes performed the four functional tests (figure 8, vertical jump, triple jump test and stairs hopple tests) twice, with an interval of mean 3.9 weeks (1-7 weeks). The reliability of the tests was determined from each tests' coefficient of variation (CV). The figure 8 test showed a significant difference between the 2 performances and the variation from test I to test II. The CV values ranged from 2.0% for the triple jump test to 7.7% for the vertical jump test. These findings do not support the reliability of the figure 8 test and the vertical jump test, but do support the reliability of the triple jump test and the stairs hopple test.